Systematic review of the influence of chemotherapy-associated liver injury on outcome after partial hepatectomy for colorectal liver metastases. Issue 8 (25th May 2017) - Zhao, J; van Mierlo, K M C; Gómez-Ramírez, J; Kim, H; Pilgrim, C H C; Pessaux, P; Rensen, S S; van der Stok, E P; Schaap, F G; Soubrane, O; Takamoto, T; Viganò, L; et al.
Abstract: Background: The impact of chemotherapy-associated liver injury (CALI) on postoperative outcome in patients undergoing partial hepatectomy for colorectal liver metastases (CRLM) remains controversial. The objective of this study was to clarify the effect of CALI (sinusoidal dilatation (SD), steatosis and steatohepatitis) on postoperative morbidity and mortality by investigating a large data set from multiple international centres. Methods: PubMed and Embase were searched for studies published between 1 January 2004 and 31 December 2013 with keywords 'chemotherapy', 'liver resection', 'outcome' and 'colorectal metastases' to identify potential collaborating centres. Univariable and multivariable analyses were performed using binary logistic regression models, with results presented as odds ratios (ORs) with 95 per cent confidence intervals. Results: A consolidated database comprising 788 patients who underwent hepatectomy for CRLM in eight centres was obtained. In multivariable analyses, severe SD was associated with increased major morbidity (Dindo–Clavien grade III–V; OR 1·73, 95 per cent c.i. 1·02 to 2·95; P = 0·043). Severe steatosis was associated with decreased liver surgery-specific complications (OR 0·52, 95 per cent c.i. 0·27 to 1·00; P = 0·049), whereas steatohepatitis was linked to an increase in these complications (OR 2·08, 1·18 to 3·66; P = 0·012). Subgroup analysis showed that lobular inflammation was the sole component associated with increased overall morbidity (OR 2·22, 1·48 to 3·34; P = 0·001) and liver surgery-specific complications (OR 3·35, 2·11 to 5·32; P < 0·001). Finally, oxaliplatin treatment was linked to severe SD (OR 2·74, 1·67 to 4·49; P < 0·001). Conclusion: An increase in postoperative major morbidity and liver surgery-specific complications was observed after partial hepatectomy in patients with severe SD and steatohepatitis. Postoperative liver failure occurred more often in patients with severe SD. Abstract : Increased complications in severe sinusoidal dilatation and steatohepatitis